2021
DOI: 10.3389/fonc.2021.628480
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals That Placenta-Specific Protein 9 Inhibits Proliferation and Stimulates Motility of Human Bronchial Epithelial Cells

Abstract: Placenta-specific protein 9 (PLAC9) is a putative secretory protein that was initially identified in the placenta and is involved in cell proliferation and motility. Bioinformatics analyses revealed that PLAC9 is repressed in lung cancers (LCs), especially lung adenocarcinomas, compared to that in the paired adjacent normal tissues, indicating that PLAC9 might be involved in the pathogenesis of pulmonary diseases. To investigate the potential role of PLAC9 in the abnormal reprogramming of airway epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Seven hundred and twenty-eight proteins were shown to be modified by 2-ClHDyA including those modified by HDyA in HSAEC. A total of 6841 proteins have been reported to be identified in human bronchial epithelial cell [ 54 ]. Thus, about 11% of HSAEC proteins are modified by 2-ClHDyA.…”
Section: Discussionmentioning
confidence: 99%
“…Seven hundred and twenty-eight proteins were shown to be modified by 2-ClHDyA including those modified by HDyA in HSAEC. A total of 6841 proteins have been reported to be identified in human bronchial epithelial cell [ 54 ]. Thus, about 11% of HSAEC proteins are modified by 2-ClHDyA.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that ISP-I suppressed cell proliferation associated with G2/M arrest. Activation of the cyclin B1/cdc2 complex is central to facilitate G2/M cell cycle transition, mainly mediated by dephosphorylation of cdc2 [42,43]. P21, as a vital member of CDK inhibitor, suppresses cyclin B1/cdc2 complex activity by interacting with many important proteins, including cdc2 and GADD45A [44], thereby inhibiting the G2/M transition in various cancer types both p53-dependent and p53-independent [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Cell counting assays were performed to detect the effects of PLAC8 on cell proliferation as previously described with minor modi cation (15,17). In 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT, Sigma, St Louis, MO, USA) assay, the cells were seeded at a density of 2,000 cells/well in 96-well tissue culture plates with 200 µL culture medium.…”
Section: Cell Proliferation Analysismentioning
confidence: 99%
“…Wound healing and invasion assays were performed as previously described with minor modi cation (17). For wound healing assay, the cells were seeded in 60 mm cell culture dishes and allowed to achieved 90% con uence.…”
Section: Cell Motility Analysismentioning
confidence: 99%
See 1 more Smart Citation